Web-based tool for analyzing the seawater-freshwater interface using analytical solutions and SEAWAT code comparison - Asaad M. Armanuos; Mohamed Selmy; Hewida Omara; Bakenaz A. Zeidan; Sobhy R. Emara (Journal of Groundwater Science and Engineering)
Saltwater Intrusion (SI) poses a significant environmental threat to freshwater resources in coastal aquifers globally. The primary objective of this research is to illustrate the variations in the saltwater-freshwater interface using several established analytical solutions, integrated within a user-friendly web-based tool. Three case studies, including a hypothetical unconfined coastal aquifer, an experimental coastal aquifer, and a real-world coastal aquifer in Gaza, were applied to examine the interface dynamics using the developed tool, built with JavaScript. To simulate variable-density flow within the Gaza coastal aquifer, the public domain code SEAWAT was employed. The resulting lengths of seawater intrusion, as simulated by SEAWAT and the observed toe length, were compared with those obtained from the web-based analytical solutions under both constant head and constant flux boundary conditions. This comparison demonstrated a strong correlation between the experimental results, SEAWAT model outputs, and analytical solutions. This research provides valuable insights into SI in coastal aquifers, with a specific focus on the impact of Sea Level Rise (SLR) on the shifting position of the seawater intrusion toe. The outcomes are presented through an accessible web-based interface, thereby promoting broader dissemination and practical application of the research outcomes.